Investigation of JAK2, STAT3 and CCR6 polymorphisms and their gene-gene interactions in inflammatory bowel disease - Polgar, N.; Csongei, V.; Szabo, M.; Zambo, V.; Melegh, B. I.; Sumegi, K.; Nagy, G.; Tulassay, Z.; Melegh, B. (International journal of immunogenetics, 2012)
Summary Genome‐wide association studies identified many loci associated with the two forms of inflammatory bowel disease (IBD), Crohn’s disease (CD) and ulcerative colitis (UC). Components of the interleukin‐23 signalling pathway, such as IL23R, JAK2 and STAT3, have been implicated in both diseases. In addition, emerging evidence supports the role of IL23‐driven Th17 cells in inflammation. Here, we studied the susceptibility nature of three components of IL23 signalling and Th17 cell differentiation: JAK2 rs10758669, STAT3 rs744166 and CCR6 rs2301436 initially associated with CD in Hungarian CD and UC patients. A total of 616 unrelated subjects with either form of IBD and 496 healthy controls were genotyped with PCR‐RFLP methods. We also tested the genetic interactions of JAK2, STAT3 and CCR6 polymorphisms in a pairwise fashion with regard to disease risk. We could confirm the susceptibility of STAT3 rs744166 TT homozygotes for UC (OR: 1.483, 95% CI: 1.103–1.992, P = 0.009). Data on genetic interaction reveals that the above JAK2 and STAT3 risk alleles contribute to CD susceptibility in combination with each other (OR: 2.218; 95% CI: 1.097–4.487; P = 0.024), while the JAK2 variant shows a tendency to confer UC risk only on a wild‐type STAT3 background (OR: 1.997, 95%CI: 0.994–4.009, P = 0.049). Our results may help in understanding how these natural variants contribute to development of IBD through their genetic association.